Plasmodium falciparum pfhrp2 and pfhrp3 Gene Deletions and Relatedness to Other Global Isolates, Djibouti, 2019–2020 - Eric Rogier; Jessica N. McCaffery; Mohamed Ali Mohamed; Camelia Herman; Doug Nace; Rachel Daniels; Naomi Lucchi; Sophie Jones; Ira Goldman; Michael Aidoo; Qin Cheng; Edie A. Kemenang; et al. (Emerging Infectious Diseases, 2022)
Deletions of pfhrp2 and paralogue pfhrp3 (pfhrp2/3) genes threaten Plasmodium falciparum diagnosis by rapid diagnostic test. We examined 1,002 samples from suspected malaria patients in Djibouti City, Djibouti, to investigate pfhrp2/3 deletions. We performed assays for Plasmodium antigen carriage, pfhrp2/3 genotyping, and sequencing for 7 neutral microsatellites to assess relatedness. By PCR assay, 311 (31.0%) samples tested positive for P. falciparum infection, and 296 (95.2%) were successfully genotyped; 37 (12.5%) samples were pfhrp2+/pfhrp3+, 51 (17.2%) were pfhrp2+/pfhrp3–, 5 (1.7%) were pfhrp2–/pfhrp3+, and 203 (68.6%) were pfhrp2–/pfhrp3–. Histidine-rich protein 2/3 antigen concentrations were reduced with corresponding gene deletions. Djibouti P. falciparum is closely related to Ethiopia and Eritrea parasites (pairwise GST 0.68 [Ethiopia] and 0.77 [Eritrea]). P. falciparum with deletions in pfhrp2/3 genes were highly prevalent in Djibouti City in 2019–2020; they appear to have arisen de novo within the Horn of Africa and have not been imported.